Interactions among Norway spruce, the bark beetle Ips typographus and its fungal symbionts in times of drought - Netherer, Sigrid; Kandasamy, Dineshkumar; Jirosová, Anna; Kalinová, Blanka; Schebeck, Martin; Schlyter, Fredrik (Journal of pest science, 2021)
Resilience and functionality of European Norway spruce forests are increasingly threatened by mass outbreaks of the bark beetle Ips typographus promoted by heat, wind throw and drought. Here, we review current knowledge on Norway spruce and I. typographus interactions from the perspective of drought-stressed trees, host selection, colonisation behaviour of beetles, with multi-level effects of symbiotic ophiostomatoid fungi. By including chemo-ecological, molecular and behavioural perspectives, we provide a comprehensive picture on this complex, multitrophic system in the light of climate change. Trees invest carbon into specialised metabolism to produce defence compounds against biotic invaders; processes that are strongly affected by physiological stress such as drought. Spruce bark contains numerous terpenoid and phenolic substances, which are important for bark beetle aggregation and attack success. Abiotic stressors such as increased temperatures and drought affect composition, amounts and emission rates of volatile compounds. Thus, drought events may influence olfactory responses of I. typographus, and further the pheromone communication enabling mass attack. In addition, I. typographus is associated with numerous ophiostomatoid fungal symbionts with multiple effects on beetle life history. Symbiotic fungi degrade spruce toxins, help to exhaust tree defences, produce beetle semiochemicals, and possibly provide nutrition. As the various fungal associates have different temperature optima, they can influence the performance of I. typographus differently under changing environmental conditions. Finally, we discuss why effects of drought on tree-killing by bark beetles are still poorly understood and provide an outlook on future research on this eruptive species using both, field and laboratory experiments.
Keywords: Picea abies; Drought; Ophiostomatoid fungi; Tree defence; Spruce bark beetle; Specialised metabolites